2008
DOI: 10.1103/physreve.78.056709
|View full text |Cite
|
Sign up to set email alerts
|

Contact line dynamics in binary lattice Boltzmann simulations

Abstract: We show that, when a single relaxation time lattice Boltzmann algorithm is used to solve the hydrodynamic equations of a binary fluid for which the two components have different viscosities, strong spurious velocities in the steady state lead to incorrect results for the equilibrium contact angle. We identify the origins of these spurious currents and demonstrate how the results can be greatly improved by using a lattice Boltzmann method based on a multiple-relaxation-time algorithm. By considering capillary f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 23 publications
2
94
0
Order By: Relevance
“…Pooley et al [133] identified that the strong spurious velocities in the steady state lead to an incorrect equilibrium contact angle for binary fluids with different viscosities. The key to reducing spurious velocities lies in the formulation of treating the interfacial tension force [134].…”
Section: Free-energy Modelmentioning
confidence: 99%
“…Pooley et al [133] identified that the strong spurious velocities in the steady state lead to an incorrect equilibrium contact angle for binary fluids with different viscosities. The key to reducing spurious velocities lies in the formulation of treating the interfacial tension force [134].…”
Section: Free-energy Modelmentioning
confidence: 99%
“…We use the binary free energy lattice Boltzmann model, first developed by Swift et al [22] and later extended by Briant et al [15] and Pooley et al [16]. The binary free energy lattice Boltzmann model includes two particle distribution functions, f i (r,t) and g i (r,t), where r denotes the position in the lattice and i is the lattice direction.…”
Section: A the Lattice Boltzmann Algorithmmentioning
confidence: 99%
“…(35) for C 0 , we have the value for the order parameter at the wall node, which is inserted to Eqs. (16) and (17) to obtain the equilibrium distribution functions. Such a value of C 0 is considered to be a "target" value for the equilibrium.…”
Section: A the Lattice Boltzmann Algorithmmentioning
confidence: 99%
See 2 more Smart Citations